2010
DOI: 10.1002/er.1798
|View full text |Cite
|
Sign up to set email alerts
|

A review of recent developments in carbon capture utilizing oxy-fuel combustion in conventional and ion transport membrane systems

Abstract: SUMMARYFossil fuels provide a significant fraction of the global energy resources, and this is likely to remain so for several decades. Carbon dioxide (CO 2 ) emissions have been correlated with climate change, and carbon capture is essential to enable the continuing use of fossil fuels while reducing the emissions of CO 2 into the atmosphere thereby mitigating global climate changes. Among the proposed methods of CO 2 capture, oxyfuel combustion technology provides a promising option, which is applicable to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
105
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(105 citation statements)
references
References 81 publications
(114 reference statements)
0
105
0
Order By: Relevance
“…Behrouzifar et al [29] suggested that if the surface reactions (13) and (14) are associated with the oxygen adsorption/dis-association on the feed side and then the oxygen recombination/desorption on the permeate side are elementary (single step) as assumed by Xu and Thomson (1999) [14] then n = 0.5. Behrouzifar et al [29] have accounted for non-elementary (multi-step) surface reactions and the derived a new value for n = 0.25.…”
Section: Mathematical Model Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Behrouzifar et al [29] suggested that if the surface reactions (13) and (14) are associated with the oxygen adsorption/dis-association on the feed side and then the oxygen recombination/desorption on the permeate side are elementary (single step) as assumed by Xu and Thomson (1999) [14] then n = 0.5. Behrouzifar et al [29] have accounted for non-elementary (multi-step) surface reactions and the derived a new value for n = 0.25.…”
Section: Mathematical Model Equationsmentioning
confidence: 99%
“…In order for the cost of ITM to be reduced and their commercialization to be feasible, next generation ITMs should achieve high permeation fluxes while operating at low temperatures. The aforementioned approaches for ITMs, if developed successfully can commercialize ITM reactor systems [13]. However, important process parameters including ion exchange at the surface, diffusion in porous media and mass transfer either by convection or diffusion should not be neglected [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is realized that oxy-fuel combustion is attracting increasing interest. Using pure oxygen instead of air for combustion generates a flue gas which consists of mainly CO 2 and H 2 O, where CO 2 can be easily captured [20][21][22][23]. Therefore, more understanding of NH 3 -SCR in the presence of an abundance of CO 2 is essential for the future development of SCR technology combined with oxy-fuel combustion processes.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 is considered to be one of the most important anthropogenic gas emission species involved in global warming (Habib et al, 2011). Oxy-fuel combustion is one of the advanced technologies used to capture CO 2 when burning fossil fuels (Buhre et al, 2005).…”
Section: Introductionmentioning
confidence: 99%